Exploring child dental service use among migrant families in metropolitan Melbourne, Australia. (19th May 2015) - Christian, B; Young, D; Gibbs, L; de Silva, A; Gold, L; Riggs, E; Calache, H; Tadic, M; Hall, M; Moore, L; Waters, E
Abstract: Background: This study describes and explores factors related to dental service use among migrant children. Methods: A cross‐sectional analysis of baseline data from Teeth Tales, an exploratory trial implementing a community based child oral health promotion intervention. The sample size and target population was 600 families with 1–4 year old children from Iraqi, Lebanese and Pakistani backgrounds residing in metropolitan Melbourne. Participants were recruited into the study using purposive and snowball sampling techniques. Results: Most (88%; 550/625) children had never visited the dentist (mean (SD) age 3.06 years (1.11)). In the fully adjusted model the variable most significantly associated with child dental visiting was parent reported 'no reason for child to visit the dentist' (OR = 0.07, p < 0.001). Of those children whose parents reported their child had no reason to visit the dentist, 22% (37/165) experienced dental caries with 8% (13/165) at the level of cavitation. Conclusions: Dental service use by migrant preschool children was very low. The relationship between perceived dental need and dental service use is currently not aligned. One in 10 children of select migrant background had visited a dentist, which is in the context of 1 in 3 with dental caries. To improve utilization, health services should consider organizational cultural competence, outreach and increased engagement with the migrant community.